Adopting an enterprise resource planning system in village government - Restu, Arnold; Gamayuni, Rindu Rika; Yuliansyah, Yuliansyah (Goodwood Publishing, 2024)
Purpose: The obligation of the Village Government to realize accountability and transparency of rural funds